2015
DOI: 10.5352/jls.2015.25.12.1393
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Production and Adipocyte Differentiation Inhibition of Low-Molecular-Weight-Alginate

Abstract: In this study, we investigated the extraction condition of alginate from Laminaria japonica, the enzymatic degradation of the extracted alginate, and the inhibitory activity of the degraded alginate on the differentiation of 3T3-L1 preadipocytes. The optimal conditions for the efficient extraction, precipitation, and recovery of alginate from the brown seaweed L. japonica were 1% for Na2CO3 concentration, 80℃ for extraction temperature, and ethanol for precipitation solvent. In the enzymatic reaction for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Injectable alginate implants have been found to possess great potential in inhibiting the damaging events after myocardial infarction, leading to myocardial repair and tissue reconstruction [6]. Park et al [7] depolymerised alginate following extraction from Laminaria japonica, and they found that the alginate lyase enzyme-treated 307 kDa alginate reduced the accumulation of lipid droplet and triglyceride in 3 T3-L1 preadipocytes in a dose-dependent manner and can be developed further for antiobesity treatment. The TNF-α secretion-inducing activity of alginate oligomers following enzymatic (lyase) hydrolysis of polyguluronate and polymannuronate differed in RAW264.7 cells and was dependent on the oligomer structures [8].…”
Section: Therapeutic Potential Of Alginatementioning
confidence: 99%
“…Injectable alginate implants have been found to possess great potential in inhibiting the damaging events after myocardial infarction, leading to myocardial repair and tissue reconstruction [6]. Park et al [7] depolymerised alginate following extraction from Laminaria japonica, and they found that the alginate lyase enzyme-treated 307 kDa alginate reduced the accumulation of lipid droplet and triglyceride in 3 T3-L1 preadipocytes in a dose-dependent manner and can be developed further for antiobesity treatment. The TNF-α secretion-inducing activity of alginate oligomers following enzymatic (lyase) hydrolysis of polyguluronate and polymannuronate differed in RAW264.7 cells and was dependent on the oligomer structures [8].…”
Section: Therapeutic Potential Of Alginatementioning
confidence: 99%
“…Research Article 270 | Journal of Conservation Science Vol.35, No.4, 2019 These substances have been used in optical films for microorganisms, pharmacological carriers (Lai et al, 2003), and membranes (Perron et al, 2002). Alginic acid with low molecular is used to suppress adipocyte differentiation (Park et al, 2015) and senescence (Choi et al, 1992) in the biomedical field. It has been used also in the agricultural field as an application composite material for eco-friendly farm materials (Kang and Jung, 2016) and as an adsorbent and a material that can be used for qualitative and quantitative analyses (Choi and Choi, 2004;Kang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%